The impact of adipokines on vascular networks in adipose tissue. (February 2023) - Vliora, Maria; Ravelli, Cosetta; Grillo, Elisabetta; Corsini, Michela; Flouris, Andreas D.; Mitola, Stefania
Abstract: Adipose tissue (AT) is a highly active and plastic endocrine organ. It secretes numerous soluble molecules known as adipokines, which act locally to AT control the remodel and homeostasis or exert pleiotropic functions in different peripheral organs. Aberrant production or loss of certain adipokines contributes to AT dysfunction associated with metabolic disorders, including obesity. The AT plasticity is strictly related to tissue vascularization. Angiogenesis supports the AT expansion, while regression of blood vessels is associated with AT hypoxia, which in turn mediates tissue inflammation, fibrosis and metabolic dysfunction. Several adipokines can regulate endothelial cell functions and are endowed with either pro- or anti-angiogenic properties. Here we address the role of adipokines in the regulation of angiogenesis. A better understanding of the link between adipokines and angiogenesis will open the way for novel therapeutic approaches to treat obesity and metabolic diseases. Graphical Abstract: Adipokines are active in the angiogenic process leading to adipose tissue homeostasis and remodeling. ga1 Highlights: The AT plasticity is strictly related to tissue vascularization. Angiogenic based therapeutic approaches may be useful to treat obesity and metabolic diseases. Adipokines govern the remodeling of stromal tissues in adipose depots.